ANALYSIS AND IMPLEMENTATION DATE MINING OF K MEAN CLUSTERING MODEL FOR CONSTRUCTION SERVICE PROVIDERS IN ASSOCIATION OF BANTEN PROVINCE CONTRACTORS - Tubagus Dian Hardiansya, Dana Santoso, Erry Rimawan (International Journal of Advanced Science and Technology, 2020)
The executor of construction services in this case is the contractor in which the contractor consists of small, medium and large classifications. The contractor is an institutional institution that acts as the executor of infrastructure project activities; the contractor consists of construction consultant services and construction implementing services. The unitary state of the Indonesian republic in the last five years has been very intensively developing infrastructure by the government. In this study trying to make a clustering model with k means clustering from construction providers in the contractor association using the WEKA application so that experts can be obtained for cluster 2, as many as 33 Provision of construction services from 98 Provision of construction services (33%), grade for cluster 4, 31 Provision of construction services from 98 Provision of construction services (30%).